Video over TETRA employing MPEG-4 visual coding standard - Chang, , YC; Beg,, MS (2004)
Video transmission over Terrestrial Trunked Radio (TETRA) mobile channel employing MPEG-4 visual coding standard is proposed in this paper. Detail parameters of the proposed systems are discussed in this paper. Performance of the proposed systems was evaluated in Average Peak Signal to Noise Ratio (APSNR) versus Signal to Noise Ratio (SNR) and Bit Error Rate (BER). In particular, the video quality that can be achieved at different channel conditions and employing different combinations of MPEG-4 visual error resilient tools is presented in this paper. Results obtained show that higher video bitrate does not necessarily lead to higher video quality at the receiver as the received video quality depends on the bit error pattern or the number of error free video packets.